A Proposed Cost-Effective Early Reading Intervention: A Tool in Improving Learners’ Reading Performance - Santos, Orlando R.; Paz, Rosalia M.; Roquero, Lorie B.; Del Rosario, Elvie B.; Del Rosario, Aileen P.; Orito, Melchy O.; Medina, Arnold B.; Victorio, Paulo A.; Cabigao, John Paul E.; Caparas, Ma. Editha R. (Future Science / FSH-PH Publications, 2025)
eading ability is a critical component of learners’ overall academic success. The effective and efficient utilization of resources is critical, especially in the new normal of education. Hence, the researchers, even in the required intervention for early-grade learners, attempted to formulate a scheme to promote better reading profiles with due consideration to school resources. Reading interventions, such as Reading Recovery, utilize one-on-one tutoring to cater to learners’ specific reading needs by evaluating reading interventions for cost and effectiveness in the specific reading skills of phonemic aware-ness, fluency, and text vocabulary, may improve their evidence-based decision-making when it comes to selecting an intervention. The researchers utilized a quasi-experimental design and purposive sampling where the whole population of interest is studied to de-termine the effectiveness of the cost-effective reading intervention A multitude of research has proven that repeated reading is an effec-tive strategy to improve fluency in struggling readers. The instru-ments employed in this study were the Early Grade Reading As-sessment tool for the pretest and the teacher-made equivalent test for EGRA for the post-test. There were 277 males and 268 females with a total of 545 grade 1-3 pupils as participants. Paired Samples T- Test utilized in the study and the results showed scores were all .000 which was less than 0.01 level of significance. Therefore, there were significant differences between the percentage scores of the pretests and the percentage scores of the post-tests. The negative sign of t- t-values indicates that the percentage scores of the post-tests were higher than the percentage scores of the pretests. Thus, the null hypothesis of no significant difference was rejected. Based on the result of this study, it can be inferred and concluded that early reading intervention in improving the learners' reading performance in terms of phonemic awareness, fluency, and text vocabulary is highly effective.